Análise dos resultados da implantação do plano de gestão de logística sustentável da Ufersa - Freitas, Mara Raquel de Sousa (Universidade Federal Rural do Semi-Árido, 2018)
Environmental management has become an essential factor in public administration, not only for portraying the effects caused to the environment as a result of organizational activities, but also to meet legal requirements that have been established by governments in the quest for sustainability. One of these devices created by the federal government to promote national sustainable development is the Plano de Gestão de Logística Sustentável - PLS, instituted by Decree nº. 7.746, dated June 5, 2012 and by Normative Instruction Nº. 10/2012, which consists of a a planning tool with defined objectives and responsibilities, actions, targets, execution deadlines and monitoring and evaluation mechanisms, which allows agencies or entities to establish sustainability practices and rationalization of expenditures and processes in the Public Administration. In this sense, the present work proposes to analyze the results of the implementation of the PLS for the environmental management of the Universidade Federal Rural do Semi-Árido - UFERSA, evaluating the implementation of the good practices of sustainability and rationalization of materials proposed in the plan with respect to electricity, water and sewage and waste management. The research is classified as exploratory, with a qualitative approach, using bibliographic and documentary research techniques, extracting in books, periodicals, dissertations, theses, manuals, reports and legislations, theoretical knowledge on the theme of sustainable development, environmental management and legal framework. Through the analysis of the collected information, it was possible to conclude that the electric energy indicator obtained satisfactory results, the indicator of water and sewage was considered insufficient, and the waste management obtained an excellent result in relation to the actions proposed by the PLS
Keywords: Gestão pública; Gestão ambiental; Plano de Gestão de Logística Sustentável - PLS; UFERSA; Mossoró/RN; Public administration; Environmental management; Plano de Gestão de Logística Sustentável - PLS; UFERSA; Mossoró/RN; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA